FIDES QUAERENS IMAGINEM: THE QUEST FOR LITURGICAL REFRAMING - Cilliers, Johan (Scriptura, 2012)
This article proposes that the theory of reframing, as developed within the context of a philosophically based theory of change, and consequently adapted by psychologists and neurological change theorists, can be useful in the quest for liturgical renewal. It elucidates this theory from an aesthetical viewpoint, referring to art works by Duchamp, Dali, and Cilliers, and distinguishes between reframing as relabeling, re-figuring, and re-signifying. Some implications are drawn in view of liturgical reframing, implementing key concepts such as re-creation, repetition, the other and wise foolishness.